KAJIAN POLA SIRKULASI MANUSIA TERHADAP KENYAMANAN PENUMPANG KERETA REL LISTRIK PADA STASIUN TANAH TINGGI KOTA TANGERANG - Ade Syoufa; Muhamad Toriq Kahfi (Jurnal Ilmiah Teknik, 2023)
Technological progress develops rapidly from time to time. Railways as a mode of transportation, especially mass transportation, cannot be separated from other modes of transportation used in the national transportation system which have their own characteristics and advantages of mass transportation. Train stations also need to further develop their potential and improve good human circulation patterns so that passengers feel comfortable. As a transit point, Tanah Tinggi Station is a class III/small train station which only has 2 railroad tracks located in Tanah Tinggi, Tangerang City. However, circulation at stations can be very ironic when public facilities at stations do not pay much attention to the use of circulation for users of rail services. The author sees many problems that arise related to human circulation for the comfort of Electric Rail Train passengers at Tanah Tinggi Station, Tangerang City. This study aims to provide an overview of human circulation patterns and spatial planning, especially at the Tanah Tinggi station, so as to obtain the concept of circulation patterns and good spatial planning to increase passenger comfort. On This research uses descriptive analysis methods carried out in 3 ways, namely, literature studies, conducting surveys of research objects, and conducting interviews with users and managers of the highland station. The research was conducted in 5 sections, (1) the main entrance of the building, (2) supporting building corridors, (3) counters, (4) ticketing areas, and (5) platforms. It can be said that the results of the analysis carried out were not good enough for passengers because they have not been able to meet the standards and eligibility according to the regulations so that the ease of circulation for pedestrians to move can be disrupted and uncomfortable.